Assessment of the equivalence and correlation between total sulfur determination methods in biodiesel: An use of isotope dilution inductively coupled plasma mass spectrometry. (15th August 2017) - de Oliveira Filho, Waldemar Pacheco; Borges, Daniel L.G.; Saint'Pierre, Tatiana Dillenburg; Dupim, Maurício; Vale, Fernanda; Marques, Bruno; Medeiros, Fabiana Rogério
Abstract: This paper describes an evaluation of current test methods for total sulfur determination in biodiesel, according to international specifications requirements, which was carried out using isotope dilution and inductively coupled plasma mass spectrometry (ID-ICP-MS) as a metrological tool. Closed vessel microwave-assisted digestion was employed using nitric acid and hydrogen peroxide as the decomposition medium, followed by isotope spike with 34 S dissolved in n-propanol. In order to overcome the spectral interference due to the presence of diatomic oxygen molecules in the ion beam, a reaction cell was used. Under optimized operating conditions, the determination of sulfur could be carried out at m / z +16, i.e., monitoring SO + signal for both sulfur isotopes. The ID-ICP-MS method was able to provide reference values for a series of commercial samples, which resulted in the evaluation of an extended concentration range. Sample sets including commercial biodiesel and inorganic sulfur-enriched biodiesel were employed as a means to evaluate the accuracy of routine methods for possible different sulfur species. No statistically significant difference was observed among the values measured with the proposed method and with the standard methods by UV fluorescence spectrometry and inductively coupled plasma optical emission spectrometry.